Probabilistic approaches for social media analysis data, community and influence - Yue, Kun 1979-; Li, Jin; Wu, Hao 1979-; Liu, Weiyi 1950-; Yin, Zidu (World scientific, 2020)
"This unique compendium focuses on the acquisition and analysis of social media data. The approaches concern both the data-intensive characteristics and graphical structures of social media. The book addresses the critical problems in social media analysis, which representatively cover its lifecycle. The must-have volume is an excellent reference text for professionals, researchers, academics and graduate students in AI and databases"--
Keywords: Social media -- Data processing; Text processing (Computer science); Quantitative research -- Statistical methods; Machine learning; Content analysis (Communication) -- Data processing; Social Media; Maschinelles Lernen; Quantitative Methode; Textanalyse